Assessment of Serum Dynamic Thiol/Disulfide Homeostasis and Oxidative/Nitrosative Stress in Patients with Crohn’s Disease - Ancel Aysun Bağdaş; Sezgin Barutçu; Ahmet Saracaloğlu; Abdullah Tuncay Demiryürek (The Turkish Journal of Gastroenterology)
Background/Aims: Crohn’s disease (CD) is a major subtype of chronic relapsing inflammatory gastrointestinal disorders. In this study, we assessed the possible contributions of serum oxidative/nitrosative stress and dynamic thiol/disulfide homeostasis to CD pathogenesis.